Secondary Metabolites of Osmanthus fragrans: Metabolism and Medicinal Value - Fu, Chen-Chen; Xu, Fa-Ying; Qian, Yu-Chen; Koo, Hoi-Lun; Duan, Yi-Fan; Weng, Geng-Min; Fan, Tai-Ping; Chen, Mo-Xian; Zhu, Fu-Yuan (Frontiers in Pharmacology, 2022)
Osmanthus fragrans (scientific name: Osmanthus fragrans (Thunb.) Lour.) is a species of the Osmanthus genus in the family Oleaceae, and it has a long history of cultivation in China. O. fragrans is edible and is well known for conferring a natural fragrance to desserts. This flowering plant has long been cultivated for ornamental purposes. Most contemporary literature related to O. fragrans focuses on its edible value and new species discovery, but the functional use of O. fragrans is often neglected. O, fragrans has many properties that are beneficial to human health, and its roots, stems, leaves, flowers and fruits have medicinal value. These characteristics are recorded in the classics of traditional Chinese medicine. Studies on the metabolites and medicinal value of O. fragrans published in recent years were used in this study to evaluate the medicinal value of O. fragrans. Using keywords such as metabolites and Osmanthus fragrans, a systematic and nonexhaustive search of articles, papers and books related to the medicinal use of Osmanthus fragrans metabolites was conducted. Fifteen metabolites were identified through this literature search and classified into three categories according to their properties and structure: flavonoids, terpenes and phenolic acids. It was found that the pharmacological activities of these secondary metabolites mainly include antioxidant, anticancer, anti-inflammatory and antibacterial activities and that these metabolites can be used to treat many human diseases, such as cancer, skin diseases, cardiovascular diseases, and neurological diseases. At present, most of the information reports on the secondary metabolites of Osmanthus fragrans have limitations. Some articles only introduce the general classification of compounds in Osmanthus fragrans, and some articles only introduce a single compound. The introduction in this paper includes both the category and the functional value of each compound. In the process of reviewing the data, the authors found that the specific action sites of these compounds and their mechanism of action in plants are still relatively weak, which should be an important topic for future research directions.